THE PHENOMENON OF DIGITAL NOMADISM IN GLOBAL MIGRATION PROCESSES: COMMUNICATION DIMENSION - Poda, Tetiana (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
In the modern world, digital technologies are changing the forms of employment, social interaction and mobility of the population. The aim is to identify the characteristics of digital nomads’ communication strategies in the processes of their professional integration, social adaptation, maintenance of cultural identity, and interaction with state institutions amid global migration changes. The tasks are 1) to identify the characteristics of the socio-cultural environment of digital nomadism in the context of globalization; 2) to explore the impact of digital nomadism on the formation of new types of social communities; 3) to outline the challenges of digital nomadism for nation-states, particularly its impact on labor markets and migration policies. Research methodology is based on poststructuralist and postmodernist mobility concepts, Deleuze and Guattari’s nomadology, Urry’s mobility paradigm, as well as the theories of Bauman, Baudrillard, and McLuhan. Research results. It is found that digital nomads form extensive professional and social networks, maintain communication through digital platforms and develop new forms of social interaction. Two groups of communication strategies have been identified: professional and labour (focused on digital platforms and work coordination) and socio-cultural (related to maintaining social ties, language adaptation and integration into digital diasporas). Discussion. Digital nomadism requires further reflection in the context of the digital economy, legal challenges and regulatory policy. Conclusions. Digital nomadism is not just a new form of mobility, but a phenomenon that is transforming social relations, economic activity and communication practices. Digital nomads form extensive communication networks that facilitate their integration into global labour markets, while at the same time facing challenges of legal status, social protection and regulation by nation-states. Their communication strategies operate on two levels: professional-labor, involving freelance platforms and remote work coordination, and socio-cultural, centered on digital diasporas that support cultural identity and adaptation in an unstable environment..